Clinical and radiological findings of posterior reversible encephalopathy syndrome in children: About 16 children hospitalized in the pediatric department of a Tunisian tertiary care hospital. (March 2023) - Ajmi, Houda; Brahim, Jawher; Mabrouk, Sameh; Ben Abdallah, Amel; Zouari, Noura; Majdoub, Fadoua; Nouir, Salsabil; Hasni, Ibtissem; Ben Cheikh, Yasser; Chemli, Jalel; Jemni, Hela; Abroug, Saoussan
Abstract: Background: Posterior reversible encephalopathy syndrome (PRES) is a clinico-radiological entity most frequently described in young- or middle-aged adults with a rare occurrence among children. Aim: To determine the clinical, radiological features and outcome of PRES in children admitted to a Tunisian tertiary care pediatric department. Methods: we retrospectively reviewed records of all children under 18 years old diagnosed with PRES and admitted to the PICU of the Pediatric department of Sahloul University Hospital from January 2000 to August 2021. Results: Sixteen patients were enrolled in this study. The mean age of the study population at PRES onset was 10 years (range: 4–14 years) and the male female ratio was 3. The most frequent neurological signs were seizures (n = 16 cases), headache (n = 8 cases), and impaired level of consciousness (7 cases). Visual disturbances were found in one patient. Arterial hypertension was the most underlying cause (16 cases). Brain MRI showed vasogenic edema, mostly localized in the parietal (13 cases) and occipital (11 cases) lobes. Moreover, cytotoxic edema (2 cases), pathologic contrast enhancement (1 case), and hemorrhage (3 cases) were isolated on MRI. The outcome after specific management was favorable after the first onset in 13 cases and death occurred in 3 patients. Relapses were observed in 4 patients. Conclusion: Clinical features presented by children with PRES are variable and non-specific. MRI typically shows reversible posterior cerebral edema. However, in some cases, atypical neuro-imaging findings, such as cytotoxic edema infarction, hemorrhage and contrast enhancement can be observed. Highlights: Symptoms presented by children with PRES are variable and non specific. MRI is a key radiological investigation that allows to exclude the differential diagnosis and then confirming PRES MRI typically shows reversible subcortical cerebral vasogenic edema. Neurological sequelae could be observed in patients presenting hemorrhage and restricted diffusion on MRI.